Central Bank Digital Currencies vs. Bitcoin: Competing or Complementary Digital Currencies? - Sidhu, Brahmaleen K (International Journal of Computer Sciences and Engineering, 2025)
With the rapid digitization of finance, Central Bank Digital Currencies (CBDCs) and Bitcoin represent two distinct approaches to digital money. CBDCs are state-backed and regulated, whereas Bitcoin is decentralized and independent of government control. Understanding their interaction is crucial for policymakers, economists, and investors. This paper conducts a comprehensive SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of both CBDCs and Bitcoin to evaluate their impact on the global financial landscape. The study explores the fundamental differences between these digital currencies, covering aspects such as monetary control, technological frameworks, regulatory challenges, and economic implications. The paper begins with an overview of related work, detailing various forms of money and existing comparative studies between CBDCs and Bitcoin. It then examines the structure, benefits, risks, and development of CBDCs, followed by an in-depth discussion on Bitcoin, including blockchain architecture, cryptographic protocols, and consensus mechanisms. Through a systematic SWOT analysis, the strengths of CBDCs—such as financial inclusion and transaction efficiency—are contrasted with their weaknesses, including privacy concerns and implementation costs. Similarly, Bitcoin’s decentralized nature and transparency are weighed against its volatility and regulatory uncertainty. Findings from this study highlight the need for balanced regulatory frameworks and technological innovations to maximize the benefits of both CBDCs and Bitcoin while mitigating associated risks. These insights contribute to ongoing discussions on the role of digital currencies in shaping the future of finance. The paper concludes with future research directions, emphasizing the importance of interoperability, scalability, and evolving security measures in the digital currency ecosystem. This research article will contribute to the ongoing debate on digital currencies, providing a balanced perspective on whether CBDCs and Bitcoin are rivals or complementary elements in the evolving financial landscape.